Design and simulation of a double boost switched capacitor multilevel inverter - Khadar, Shaik Abdul; Shuaib, Yassin Mohamed; Arun, Vijayakumar; Karakilic, Murat; Rahul, Jammy Ramesh (Institute of Advanced Engineering and Science, 2025)
This article presents an innovative boost inverter configuration that produces a nine-level double voltage augmentation waveform. A significant drawback of conventional multilevel inverters (MLIs) lies in their dependence on conversion for elevating the voltage, particularly applied in conjunction with renewable energy sources. The proposed methodology, characterized by its double voltage boosting capacity, mitigates this challenge by automatically enhancing the input voltage. Switched-capacitor multilevel inverters (SCMLIs) represent a prevalent category within the realm of MLIs. This paper presents a double boost switched capacitor inverter (DB-SCI) designed to address critical issues involving the increased use of semiconductor switches, DC sources, and capacitors. The proposed DB-SCI achieves a nine-level resultant voltage utilizing a single DC source, 8 switches, and 3 capacitors. It can amplify the output voltage with a gain of two. Moreover, the DB-SCI employs a level-shifted pulse width modulation (PWM) approach to augment the resultant voltage and enhance the output voltage's quality. The article assesses the effectiveness and feasibility of the DB-SCI under various modulation indices using MATLAB/Simulink. The comparison study of MLI topologies is presented.